China-EU paradiplomacy to fight climate change - Suszwalak, Oliwia; Filipińska, Aleksandra (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
China is one of the most polluted countries in the world. The Chinese government is undertaking numerous efforts to improve the state of the environment. However, there is also a noticeable increase in the activity of local governments in this area, which are beginning to collaborate with cities worldwide, including in Europe. The aim of this chapter is to present Sino-EU city cooperation in combating climate change. It will outline the characteristics of paradiplomacy and its significance for the development of low-emission cities, EU-China city-level cooperation, as well as selected examples highlighting the importance of the roles played by EU and Chinese cities in combating climate change. This will enable addressing questions regarding the role of paradiplomacy in environmental protection, the forms of cooperation established by cities with the EU and China, as well as whether this cooperation is effective and what challenges it encounters.